PENGARUH SERBUK DAUN MAJAPAHIT (crescentia cujete L) TERHADAP IKAN NILA (oreochromis niloticus) YANG TERJANGKIT PENYAKIT MAS (motile aeromonas septicemia) - Rahmaningsih, Sri; Wahyuni, Novi Febri; suwrsih (Universitas Hang Tuah, 2021)
MAS (Motile aeromonas septicemia) disease is a disease caused by Aeromonas hydrophil bacteria which usually attacks fish in the waters and often results in mass death. Several types of plants are known to treat the disease, including Majapahit leaves (Crescentia cujete L). The purpose of this study was to determine the effect of majapahit leaf powder (Crescentia cujete L) on tilapia (Oreochromis niloticus) which had been infected by MAS (Motile aeromonas septicemia). The research method uses a completely randomized design (CRD) with three treatments and four replications namely; treatments A (7.5%), B (10%), and treatment C (12.5%). The results showed the right dose to increase SR Survive rate and the highest phagocytosis index in tilapia was in C treatment, which was the addition of 12.5% ​​of Majapahit leaf powder to feed.